SISTEM BUDIDAYA TERKONTROL UNTUK MENINGKATKAN KESEHATAN IKAN GURAMI : Controlled Cultivation System To Improve The Health Of Gurami Fish - Hifzon, Lalu Ahmad; Aminullah, Aminullah (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
This research aims to improve the health of gourami fish using a controlled cultivation system. This research is participatory research, researchers took part in all activities at the Lingsar Fish Seed Center (BBI) West Lombok. Data collection methods are by observation and documentation. The data obtained was analyzed using descriptive statistics. The data collected regarding fish health includes feed, containers or ponds and water quality. The research results show that the controlled cultivation system is carried out naturally starting from pond preparation, pond drying